Automated Facial Recognition in Law Enforcement: The Queen (On Application of Edward Bridges) v The Chief Constable of South Wales Police - Gordon, Barrie (Potchefstroom Electronic Law Journal, 2021)
The use of automated facial recognition in law enforcement is still a novel practice and as a result the legislative framework for this technology is ill-defined. The judgement of The Queen (on application of Edward Bridges) v The Chief Constable of South Wales Police [2020] EWCA Civ 1058 is the first case in the world that examines pertinent legal questions pertaining to this new technology. Automatic facial recognition may be used in law enforcement, but to prevent massive human rights violations, operators should perform their duties within a well-defined legal framework where discretion is kept to the minimum, and strict data-retention policies are followed. Furthermore, human oversight should always be part of an automated facial recognition system to ensure accuracy, fairness, and compliance with the law.